A Theory of ICOs: Diversification, Agency, and Information Asymmetry - Chod, Jiri; Lyandres, Evgeny (Management Science, 2021)
This paper develops a theory of financing of entrepreneurial ventures via crypto tokens, which is not limited to platform-based ventures. We compare token financing with traditional equity financing, focusing on agency problems and information asymmetry frictions associated with the two financing methods, as well as on risk sharing between entrepreneurs and investors. Token financing introduces an agency problem not present under equity financing (underproduction), while mitigating an agency problem often associated with equity financing (entrepreneurial effort underprovision). Our theory abstracts from all institutional and potentially transient differences between tokens and equity and is based on a single intrinsic characteristic of tokens: they represent claims to a venture’s output. We show that tokens are likely to dominate equity for ventures developing goods or services that involve low marginal production costs, those for which entrepreneurial effort is crucial, and/or those with relatively low payoff volatility. In addition, tokens can have an advantage over equity in signaling venture quality to outside investors. This paper was accepted by Kay Giesecke, finance.